Handling, Processing and Composition of Cow Milk Under Two Traditional Farming Systems in Kebribeyah District of Fafan Zone, Somali Regional State, Ethiopia (American Journal of Aquaculture and Animal Science, 2023)
The aim of this study was to assess handling, processing & chemical composition of cow milk in Kebribeyah district. The study had a survey and laboratory works. For the survey study, two production systems namely pastoral and agro-pastoral were considered. From each production system, two kebeles were selected purposively based on accessibility and potential of cow milk production. One hundred twenty households were randomly selected from purposively selected kebeles. For the laboratory part, forty samples of cow milk were analysed for chemical composition. The overall average lactation length and daily milk off-take of cow in this study were 256 days and 2.06 litres, respectively. None of the respondents washed the udder of the cow and only 6.7% of the pastoralists and 20% agro-pastoralists wash their hands before milking. Milk handling equipment were mainly plastic materials. Acacia ethaica, B. minimifolia, Blanites galabra and Solanum carense were the most commonly used smoking plant species in the area. The majority of the respondents (85.8%) produced traditional butter (Subag) and few households (10%) produced sour milk (Ciir), while very few (4.2%) households produced traditional cheese (Burcad). However, milk processing in the area is limited to wet season; when there is abundance of fodder. The average values of total solids, fat, protein, lactose and ash were 13.19%, 4.67%, 3.45%, 5.18% and 0.72%, respectively. However, significance differences (P